Transforming healthcare through a digital revolution: A review of digital healthcare technologies and solutions - Naik, Nithesh; Hameed, B. M. Zeeshan; Sooriyaperakasam, Nilakshman; Vinayahalingam, Shankeeth; Patil, Vathsala; Smriti, Komal; Saxena, Janhavi; Shah, Milap; Ibrahim, Sufyan; Singh, Anshuman; Karimi, Hadis; Naganathan, Karthickeyan; et al. (Frontiers in Digital Health, 2022)
The COVID-19 pandemic has put a strain on the entire global healthcare infrastructure. The pandemic has necessitated the re-invention, re-organization, and transformation of the healthcare system. The resurgence of new COVID-19 virus variants in several countries and the infection of a larger group of communities necessitate a rapid strategic shift. Governments, non-profit, and other healthcare organizations have all proposed various digital solutions. It's not clear whether these digital solutions are adaptable, functional, effective, or reliable. With the disease becoming more and more prevalent, many countries are looking for assistance and implementation of digital technologies to combat COVID-19. Digital health technologies for COVID-19 pandemic management, surveillance, contact tracing, diagnosis, treatment, and prevention will be discussed in this paper to ensure that healthcare is delivered effectively. Artificial Intelligence (AI), big data, telemedicine, robotic solutions, Internet of Things (IoT), digital platforms for communication (DC), computer vision, computer audition (CA), digital data management solutions (blockchain), digital imaging are premiering to assist healthcare workers (HCW's) with solutions that include case base surveillance, information dissemination, disinfection, and remote consultations, along with many other such interventions.